Y2K Options and the Liquidity Premium in Treasury Markets - Sundaresan, Suresh; Wang, Zhenyu (Review of Financial Studies, 2009)
[Financial institutions around the world expected the millennium date change (Y2K) to cause an aggregate liquidity shortage. Responding to the concern, the Federal Reserve Bank of New York auctioned Y2K options to primary dealers. The options gave the dealers the right to borrow from the Fed at a predetermined interest rate. Using the implied volatilities of Y2K options and the on/off-the-run spread, we demonstrate that the Fed's action eased the fears of bond dealers, contributing to a drop in the liquidity premium of Treasury securities. Our analysis shows the link between the microstructure of government debt markets and the central bank's provision of liquidity. We argue that Y2K options and their effects on liquidity premium broadly conform to the economic theory on public provision of private liquidity.]